Religious tourism in Egypt: a case study analysis - Ali, Mohamed Mostafa (AUC Knowledge Fountain, 2013)
Egyptian tourism has seen cases of rise and fall. The difference in the numbers of tourists from both inside and outside Egypt leads to the difference in the revenues generated by tourism and consequently affects the rate of growth in Egypt. This study aims at shedding light on the elements of religious tourism and identifying the possibility for Egypt to occupy a leading position among the religion tourism. This study compares Egyptian tourism revenues with the revenues achieved by some top-ranking countries. The steps Egypt has to follow, in order to achieve the desired progress and a reasonable ranking, are also discussed. In addition, some interviews and visits to some tourist companies were conducted in order to identify the religious tourism programs they offer and clarify their role in the development of the tourism industry in Egypt. This study aims also at finding out the role of the Egyptian government, the Ministry of Interiors and ordinary citizens in the development and progress of religious tourism in Egypt. It also clarifies the difference in the views of religious political parties in Egypt on religious tourism.